A stumbling block in pancreatic cancer treatment: drug resistance signaling networks - Liu, Jinming; Zhang, Biao; Huang, Bingqian; Zhang, Kexin; Guo, Fujia; Wang, Zhizhou; Shang, Dong (Frontiers in Cell and Developmental Biology, 2025)
The primary node molecules in the cell signaling network in cancer tissues are maladjusted and mutated in comparison to normal tissues, which promotes the occurrence and progression of cancer. Pancreatic cancer (PC) is a highly fatal cancer with increasing incidence and low five-year survival rates. Currently, there are several therapies that target cell signaling networks in PC. However, PC is a “cold tumor” with a unique immunosuppressive tumor microenvironment (poor effector T cell infiltration, low antigen specificity), and targeting a single gene or pathway is basically ineffective in clinical practice. Targeted matrix therapy, targeted metabolic therapy, targeted mutant gene therapy, immunosuppressive therapy, cancer vaccines, and other emerging therapies have shown great therapeutic potential, but results have been disappointing. Therefore, we summarize the identified and potential drug-resistant cell signaling networks aimed at overcoming barriers to existing PC therapies.